Complex assembly, crystallization and preliminary X‐ray crystallographic analysis of the chicken MHC class I molecule BF2*1501. Issue 2 (5th February 2013) - Sun, Beibei; Li, Xiaoying; Wang, Zhenbao; Xia, Chun
<x xml:space="preserve">Abstract</x> The chicken major histocompatibility complex (MHC) class I molecules named BF are strongly associated with Marek's disease (MD). A single structure, that of chicken BF2*2101 from the B21 haplotype, which might provide resistance to MD, has been determined. However, little is known about other structures apart from BF2*2101. In order to provide further structures of chicken MHC class I molecules, BF2*1501 and chicken β2‐microglobulin complexed with a nonapeptide (MDV‐MEQRRR9) derived from Marek's disease virus MEQ protein (MDV EcoRI Q fragment, residues 72–80) were assembled and crystallized. Diffraction data from the crystal were collected to 2.6 Å resolution; the crystal belonged to space group P3121, with unit‐cell parameters a = 125.1, b = 125.1, c = 80.9 Å and two molecules in the asymmetric unit. The Matthews coefficient VM was 2.08 Å3 Da−1, with a calculated solvent content of 40.78%. These data will be helpful in obtaining insight into the structural basis of the involvement of BF2*1501 in MD.